The mediating effect of customer sociability on the relationship between digital marketing and customer engagement - Faraj Aldaihani, Faraj Mazyed (Inderscience Publishers, 2024)
The focus of the current study is to highlight the impact of digital marketing on customer behaviour. It was hypothesised that mobile marketing and social media marketing have significant effects on customer engagement through customer sociability using a sample of university students. The sample of this study consists of university students in Kuwait. Two-hundred eleven students agreed to participate in the study based on the results of a convenience sampling technique undertaken via online administration of the questionnaire of the study. Data were collected using a questionnaire adapted from previous studies, and analysed by IBM SPSS 25.0 AMOS 22.0. The results indicated that mobile marketing and social media marketing had significant effects on customer satisfaction. Furthermore, the results confirmed that customer sociability significantly mediated the effects of both mobile marketing and social media marketing on customer engagement. It was recommended that firms should paid more attention to digital marketing tools as well as customer sociability to ensure sufficient benefits of digital marketing implementation.